Workflow Analysis Comparing Manual and Automated Specimen Processing for Mass Spectrometry–Based Vitamin D Testing. - Hermes Tacker, Danyel; Topardo, Joyce; Mahaffey, Carole; Perrotta, Peter L. (Laboratory Medicine)
Objective: To quantify the benefits of automating specimen extraction in terms of specimen-preparation times and labor usage. Methods: We used workflow modeling and time-motion studies to compare manual and automated solid-phase extraction methods to prepare specimens for a mass spectrometry–based vitamin D assay. We processed 20 batches, that included 5 to 90 specimens each, with both methods in parallel and randomly over a 4-week period. Technologist discomfort/fatigue was subjectively measured. Results: Batch preparation time, per-specimen processing time, and labor requirements were significantly lower for all batch sizes on the Tecan Freedom EVO 150 robotic liquid-handling system (EVO). Technologist fatigue was significant when batch sizes reached 60 specimens. Cycle times were more uniform on the EVO. Automation provided as many as 85 minutes of useable technologist idle time for the 90-specimen batch. Conclusions: Automated specimen preparation should be considered when batch sizes reach 35 to 40 specimens per day.